Analisis Uji Kinerja Bank Syariah Menggunakan Maqashid Syariah Index dan Islamicity Performance Index (Studi pada Bank Umum Syariah tahun 2021-2024) - Nada Annisa; Evi Ekawati; Is Susanto (Yayasan Pendidikan Penelitian Pengabdian Algero, 2025)
This study aims to examine and compare the performance of Islamic commercial banks in Indonesia with the approach of Maqashid Syariah Index (MSI) and Islamicity Performance Index (IPI) as an alternative measurement that integrates the spiritual, social, and economic dimensions in accordance with the principles of Sharia. A descriptive quantitative approach was used in analyzing secondary data obtained from the annual reports of 13 Islamic commercial banks registered with the Financial Services Authority (OJK) during the period 2021-2024. The results showed that although most banks showed progress in the dimensions of profitability and transparency, there were still significant weaknesses in education, research, and social distribution indicators indicating that the implementation of sharia principles as a whole was not optimal. BPD NTB Syariah consistently ranks highest in most indicators as the BEST BUS in the achievement of the Maqashid Syariah Index (MSI) in the 2021-2024 period of 37.39%. Supported by the achievement of bpd NTB Syariah which has a high average value of 31.55%, while small banks tend to experience gaps in the implementation of Sharia objective values. Bank Aladin Syariah was identified as the BEST BUS based on Overall IPI with an average of 40.12%. The findings underscore the urgency of adopting maqashid-oriented measurement systems and Sharia integrity in banking managerial and regulatory strategies. Therefore, this study recommends the integration of MSI and IPI as a framework for evaluating the performance standards of Islamic banks to encourage the achievement of economic, spiritual, and social sustainability in the Islamic banking industry.